Thymoma Presenting as a Giant Intrathoracic Mass (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Thymoma is an epithelial neoplasm of the thymus, which commonly lies in the anterior mediastinum. Thymomas comprise about 1% of all mediastinal tumours. The current treatment of invasive thymoma is often multidisciplinary. This report presents a case of giant thymoma arising in the anterior mediastinum. Surgical resection was scheduled based on the radiological and fine needle aspiration cytology findings. The tumor was completely resected. The weight of the tumor was 2000g. The tumor was histologically diagnosed to type B1 thymoma. Patient was discharged from hospital with advice to attend the oncology department for next treatmentJ Bangladesh Coll Phys Surg 2016; 34(1): 37-41